Fabrication and Study on One-Transistor-Capacitor Structure of Nonvolatile Random Access Memory TFT Devices Using Ferroelectric Gated Oxide Film - Cheng, Chien-Min; Chen, Kai-Huang; Lin, Chun-Cheng; Chen, Ying-Chung; Chen, Chih-Sheng; Chang, Ping-Kuan (IntechOpen, 2011)
None